Perancangan Media Pembelajaran Bangun Ruang Berbasis Augmented Reality (AR) Menggunakan Unity 3D di SMP Negeri 2 Payakumbuh - Eriani, Gita; Efriyanti, Liza (Lembaga Yasin AlSys, 2025)
This study aims to design Augmented Reality (AR)-based Space Building learning media using Unity 3D to improve learning effectiveness at SMP Negeri 2 Payakumbuh. The method used is Research and Development (R&D) with the Hannafin and Peck model, which includes three stages: Need Assessment, Design, and Develop/Implement. The learning media is designed to provide an interactive learning experience by displaying virtual space objects, which can be accessed both inside and outside the classroom. Media testing includes validity test using Aiken's V, practicality test using kappa moment, and effectiveness test using G-Score. The validity test results by four validators showed an average value of 0.83 (valid category), the practicality test by two teachers and ten students resulted in an average value of 0.80 (high category), and the effectiveness test by twenty students obtained an average value of 0.71 (high effectiveness category). The results show that this AR-based learning media can be used by teachers and students to understand Spatial Buildings material more effectively. This finding is expected to be an innovative solution in the development of interactive learning media.